Antithyroid treatment improves thrombocytopenia in a young patient with graves’ disease - Faienza, Maria Felicia; Palmieri, Viviana Valeria; Chiarito, Mariangela; Lassandro, Giuseppe; Giordano, Paola (Acta Biomedica Atenei Parmensis, 2020)
Autoimmune thyroid disorders, including Graves’ disease and Hashimoto’s thyroiditis, have been reported in patients with primary immune thrombocytopenia (ITP). Several etiopathogenetic mechanisms connecting thyroid diseases and thrombocytopenia have been described. Thrombocytopenia is often documented in patients with Graves’ disease, due to reduced platelet life span in hyperthyroidism, immune dysregulation and genetic predisposition (HLA B8 presence). We present the case of a 14-years old girl, who was referred to our Pediatrics Unit, because of contemporary appearance of weight loss, profuse sweating and episodes of recurrent epistaxis. A complete health team, made up of hematologists and endocrinologists, met in consultation in order to reach a diagnosis. A suppression of serum TSH concentrations, the presence of anti-TSH receptor antibodies, and at the same time an immune thrombocytopenia with positive anti-platelet antibodies, have been detected. Furthermore, a positive direct and indirect Coombs test without hemolytic anemia, ANA positivity, and a C4 consumption have been documented. The patient started treatment with thiamazole with progressive improvement of thyroid function and thrombocytopenia, requiring only an intravenous immunoglobulin infusion on one time. A multidisciplinary follow-up has been scheduled, in order to monitor the multi-organ immune dysregulation. This report documents a significant improvement of thrombocytopenia after antithyroid treatment in a young subject affected with Graves’ disease.